OCCUPATIONAL THERAPY (GARDENING PAKKCOY PLANT) TOWARDS SELF ESTEEM OF PEOPLE WITH MENTAL ILLNESS AT PUBLIC HEALTH CENTER WORKING AREA OF KOTA GEDE 1 YOGYAKARTA - Cristin Wiyani; Endang Nurul Syafitri; Titiani Titiani (Jurnal Keperawatan Respati Yogyakarta, 2021)
Mental health problems in Indonesia were important public health cases which needed to be concerned. One of these cases was the people with mental illness. Based on preliminary study with People with Mental Illness (ODGJ), these people did not work, did not have skills, they were only at home, did not participate in any activities in their environment due to lack of confidence. The impact of unhandled confidence, these people would socially isolate themselves, and they did not have confidence. The most efficient handling was non-pharmacological therapy. One of non-pharmacological therapy was occupational therapy. This therapy was an activity which could increase confidence. The objective of Study to find out the impact of occupational therapy (gardening pakcoy plant) towards the pride of people with mental illness. This study was quasi experimental research which used pre-test and post-test without control design. The data sampling used Non Probability Sampling technique with Quota Sampling method. The total samples were 14. Besides, the instrument of this study was Rosenberg Self-Esteem Scale questionnaire. The bivariate analysis which was used this study was Wilcoxon test. The pride of people with mental illness in Purbayan Urban Village before it was given the therapy was around 22.29, and after therapy was around 32. 43. It showed that there was an increasing number of mean pre-test and mean post-test values. The impact of occupational therapy towards the pride of people with mental illness was obtained the value of p-value 0.001/<0.05. There was an impact of Occupational Therapy (gardening bok choy plant) towards the pride of people with mental illness. Keywords: Occupational Therapy; Pride; People with Mental Illness (ODGJ)